Optimizing rate and time of nitrogen application for reducing nitrogen requirement and increasing productivity of wheat - Shaikh, Abu Sufian; Khatun, Mahfuza; Ali, Md Yasin; Sarker, Bidhan Chandro (Fundamental and Applied Agriculture, 2023)
As per 4Rs nutrient stewardship, the right timing and right rate of nitrogen (N) are two important attentions for profitable and sustainable crop production, particularly in the N deficient soil. The effectiveness of N utilization depends on the appropriate timing and amount of N application as per the crop demands at the critical stages of crop growth. The experiment was carried out at the experimental field of Agrotechnology Discipline, Khulna University, Bangladesh during the winter season of 2019-20 to investigate into the effect of schedule and rates of N application on wheat growth, yield and profitability. The experimental treatments comprised three application schedules (66% at sowing and 34% at the 3-leaf stage; 50% at 3-leaf, 30% at jointing and 20% at the booting stage; 50% at 6-leaf stage, 30% at jointing and 20% at the booting stage) and three nitrogen rates (120, 92 and 80 kg ha-1) with three replications. The yield attributes and yield of wheat were substantially affected by the schedule and rates of N application yet growth parameters were not significant. The highest grain yield, total dry matter, grains spike-1 and 1000-seed weight were achieved from the application of N @ 50% at 3-leaf, 30% at jointing and 20% at booting stages with 120 kg ha-1. Statistically similar results were also attained by the same application schedule with a reduced rate of N (92 kg ha-1) due to proper distribution based on the crop requirement on different growth stages rather than the usual practice with a higher rate of N. The maximum net return (BDT 50687) and benefit-cost ratio (1.62) were found in the application of 92 kg ha-1 N in three splits @ 50% at 3-leaf, 30% at jointing and 20% at booting stages. The findings of this study revealed that the right application schedule reduces 25% N requirement and increases the grain yield of wheat.